Penerapan Security System Pada Perangkat Teknologi CCTV (Closed-Circuit Television) Bagi Siswa di SMK Al-Ikhlas - Wahyu Hidayat; R Joko Sarjanoko; Farhan Zayid; Syafrial; Ardin Hersandini; Ando Fernando; Diego Fauzi (LP3M Universitas Binaniaga Indonesia, 2025)
The training on CCTV technology at Al-Ikhlas Vocational School in Cisarua, Bogor, aims to enhance students' skills in designing security systems. This activity includes socialization, intensive training, technology implementation, as well as mentoring and evaluation. Students are introduced to the fundamentals of security systems, their types and models, and trained to design systems using CCTV devices creatively and innovatively. They are also encouraged to apply these skills in school activities, such as security monitoring through CCTV applications. The training results showed a significant improvement in students' ability to use CCTV devices, including designing systems that meet their needs. The final evaluation revealed that students not only understand the basic components and features of CCTV but are also capable of developing innovative ideas independently. This program has created an interactive and collaborative learning environment, boosting students' confidence in utilizing security technology. As a sustainability initiative, the formation of an extracurricular activity focusing on security system implementation in schools is proposed.